2011
DOI: 10.1530/eje-10-0736
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 and type 2 iodothyronine deiodinases in the thyroid gland of patients with 3,5,3′-triiodothyronine-predominant Graves' disease

Abstract: Objective: 3,5,3 0 -triiodothyronine-predominant Graves' disease (T 3 -P-GD) is characterized by a persistently high serum T 3 level and normal or even lower serum thyroxine (T 4 ) level during antithyroid drug therapy. The source of this high serum T 3 level has not been clarified. Our objective was to evaluate the contribution of type 1 and type 2 iodothyronine deiodinase (D1 (or DIO1) and D2 (or DIO2) respectively) in the thyroid gland to the high serum T 3 level in T 3 -P-GD. Methods: We measured the activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 26 publications
(42 reference statements)
1
25
0
Order By: Relevance
“…Independently of the genesis of the hyperthyroidism, PTU resulted in a reduction of the T4-to-T3 conversion to 47% of the initial value, while adding sodium ipodate caused a further decrease in the ratio to 34 % of the initial value. These results suggest that the major source of the excess T3 was D1-mediated T4 monodeiodination (50%), with a minor role for D2 (15-20%) (78,79).…”
Section: Deiodinases and Hyperthyroidismmentioning
confidence: 85%
“…Independently of the genesis of the hyperthyroidism, PTU resulted in a reduction of the T4-to-T3 conversion to 47% of the initial value, while adding sodium ipodate caused a further decrease in the ratio to 34 % of the initial value. These results suggest that the major source of the excess T3 was D1-mediated T4 monodeiodination (50%), with a minor role for D2 (15-20%) (78,79).…”
Section: Deiodinases and Hyperthyroidismmentioning
confidence: 85%
“…Maia et al (16) reported that D2 is expressed in the human thyroid gland and is postulated to play an important role as a source of plasma T 3 . As a matter of fact, it has been suggested that the increased D2 in the thyroid gland may account for the status of a low FT 4 with relatively high or normal circulating T 3 levels in other thyroid diseases, such as follicular carcinoma (10), thyroglobulin gene abnormalities (17), and T 3 -predominant Graves' disease (18). Very recently, Hoermann et al reported the association between thyroid volume and deiodinase activity.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…Some recent studies reported an interesting similarity in gene expression between tissues from T 3 predominant Graves' disease and hyperfunctioning adenomas. They overexpress not only iodothyronine deiodinases but also N-cadherin (CDH2) [54,55]. If T 3 predominant Graves' disease is caused by an increased number of fetal thyroid cells, probably prothyrocytes, some clinical features of T 3 -predominant Graves' disease, such as its high prevalence in the young and tendency to form a large goiter, are easily explained.…”
Section: Some Questions Remain To Be Clarified In the Fetal Cell Carcmentioning
confidence: 99%